Benefits of Vitamin D Supplementation on Pregnancy of Rats with Pregestational Diabetes and Their Offspring - Klöppel, Eduardo [UNESP]; Sinzato, Yuri K. [UNESP]; Rodrigues, Tiago; Gallego, Franciane Q. [UNESP]; Karki, Barshana [UNESP]; Volpato, Gustavo T.; Corrente, José E. [UNESP]; Roy, Sayon; Damasceno, Débora C. [UNESP] (Springer Nature, 2022)
Studies on vitamin D supplementation have been performed in experimental and clinical investigations considering gestational diabetes and/or vitamin D deficiency in pregnancy. However, the results are controversial and few present the effects and mechanisms of this micronutrient on pregestational diabetes. The objective of this study was to evaluate the effect of vitamin D on the pregnancy of rats with pre-existing diabetes and their fetuses. Pregestational diabetes was induced in Sprague–Dawley rats at birth. The adult diabetic and nondiabetic rats were orally administered with vitamin D (cholecalciferol) throughout the pregnancy. The diabetes status was monitored during pregnancy by an oral glucose tolerance test (OGTT). At the end of the pregnancy, pancreas and blood samples were collected for morphological analyses and lipid peroxidation measurements, respectively. The influence of vitamin D treatment on reproductive outcomes, fetal growth, and development were compared to those of untreated diabetic and nondiabetic pregnant rats. P < 0.05 was considered a significant statistical limit. The diabetic rats given vitamin D had a greater number of insulin-positive cells, contributing to reduced blood glucose levels and thiobarbituric acid reactive substance concentrations (TBARS—an indicator of membrane lipid peroxidation), and increased reduced thiol group levels, contributing to suitable intrauterine conditions for better fetal development, which was confirmed by higher fetal viability rates. Thus, this study shows the effects and mechanisms of vitamin D supplementation on pre-existing diabetes in pregnant rats, confirming its beneficial effects on maternal redox status and glycemic control, and the decline of adverse maternal–fetal repercussions.
Keywords: Diabetes; Fetuses; Murine; Oxidative redox; Pregnancy; Vitamin D